Environmental policy relating to domestic laundry in the European Union. (4th August 2014) - Morse, G.K.; Perry, R.; Lester, J.N.
Environmental policy relating to consumer markets usually focuses on the impact of products. However, it may be possible to develop more effective policies by focusing more broadly on consumer activities for which a range of products may be used. This study evaluates the total environmental impact of domestic laundering in the European Union (EU), assessing the relative impact of textiles, washing machines, energy, water and detergents, and considering their influence on each other. It is concluded that, in relation to the total environment, only a minor contribution can be made by policies targeted at laundry–related products. However, the most effective policy initiatives should be based on use minimisation, the use of more efficient washing machines, optimum use of detergents, and effective implementation of the Urban Wastewater Directive. This emphasis contrasts with the historical focus on detergent ingredients.